Hubungan kualitas pelayanan kesehatan dengan tingkat kepuasan pasien rawat jalan BPJS - Candra Ari Zoga; Yuni Kurniasih; Noor Ariyani Rokhmah (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Patient satisfaction is an indicator of healthcare services because it reflects the match between expectations and the service received. Based on the patient satisfaction rate at Playen 1 Community Health Center in the first semester of 2025, it was 84.39%. This result indicates that service quality remains below the minimum service standard set by the Indonesian Minister of Health Regulation in 2016, which is >95%. Purpose: To determine the relationship between the quality of health services and the level of satisfaction of BPJS outpatients. Method: This study was a quantitative study with a descriptive correlation design using a cross-sectional approach. A sample of 106 respondents was selected using a purposive sampling technique. Data collection was conducted using a questionnaire on health service quality and patient satisfaction. Data analysis was performed using the Spearman Rank test. Results: The majority of health service quality respondents stated that it was in the very good category, with 97 respondents (91.5%). Patient satisfaction was mostly in the very satisfied category, with 98 respondents (92.5%). Data analysis yielded a p-value of 0.001 <0.05 and a correlation coefficient of 0.817, indicating a significant, positive, and very strong relationship. Conclusion: There is a significant, positive, and very strong relationship between the quality of healthcare services and the satisfaction level of BPJS outpatients. Keywords: BPJS; Community Health Center; Outpatient Care; Patient Satisfaction; Quality Of Service. Pendahuluan: Kepuasan pasien menjadi indikator pelayanan kesehatan karena mencerminkan kesesuaian antara harapan dan pelayanan yang diterima. Berdasarkan tingkat kepuasan pasien di Puskesmas Playen 1 pada semester I tahun 2025 sebesar 84.39%. Hasil tersebut menunjukkan kualitas pelayanan masih berada dibawah nilai standar pelayanan minimal yang ditetapkan PERMENKES RI tahun 2016 yaitu >95%. Tujuan: Untuk mengetahui hubungan kualitas pelayanan kesehatan dengan tingkat kepuasan pasien rawat jalan BPJS. Metode: Penelitian ini merupakan penelitian kuantitatif dengan desain deskriptif korelasi menggunakan pendekatan cross-sectional. Sampel berjumlah 106 responden yang dipilih menggunakan teknik purposive sampling. Pengumpulan data dilakukan menggunakan kuesioner kualitas pelayanan kesehatan dan kepuasan pasien. Analisis data dilakukan menggunakan uji Spearman Rank. Hasil: Kualitas pelayanan kesehatan mayoritas menyatakan kategori sangat baik sebanyak 97 responden (91.5%). Kepuasan pasien mayoritas menyatakan kategori sangat puas sebanyak 98 responden (92,5%). Hasil analisis data didapatkan hasil p-value 0.001<0.05 dan nilai koefisien korelasi sebesar 0.817 artinya terdapat hubungan signifikan, positif, dan sangat kuat. Simpulan: Terdapat hubungan signifikan, positif, dan sangat kuat antara kualitas pelayanan kesehatan dengan tingkat kepuasan pasien rawat jalan BPJS. Kata Kunci: BPJS; Kepuasan Pasien; Kualitas Pelayanan; Puskesmas; Rawat Jalan.